Calcium plus vitamin D supplementation and risk of fractures: an updated meta-analysis from the National Osteoporosis Foundation - Weaver, C.; Alexander, D.; Boushey, Carol; Dawson-Hughes, B.; Lappe, J.; LeBoff, M.; Liu, S.; Looker, A.; Wallace, T.; Wang, D. (Springer, 2016)
Summary: The aim was to meta-analyze randomized controlled trials of calcium plus vitamin D supplementation and fracture prevention. Meta-analysis showed a significant 15 % reduced risk of total fractures (summary relative risk estimate [SRRE], 0.85; 95 % confidence interval [CI], 0.73–0.98) and a 30 % reduced risk of hip fractures (SRRE, 0.70; 95 % CI, 0.56–0.87). Introduction: Calcium plus vitamin D supplementation has been widely recommended to prevent osteoporosis and subsequent fractures; however, considerable controversy exists regarding the association of such supplementation and fracture risk. The aim was to conduct a meta-analysis of randomized controlled trials [RCTs] of calcium plus vitamin D supplementation and fracture prevention in adults. Methods: A PubMed literature search was conducted for the period from July 1, 2011 through July 31, 2015. RCTs reporting the effect of calcium plus vitamin D supplementation on fracture incidence were selected from English-language studies. Qualitative and quantitative information was extracted; random-effects meta-analyses were conducted to generate summary relative risk estimates (SRREs) for total and hip fractures. Statistical heterogeneity was assessed using Cochran’s Q test and the I2 statistic, and potential for publication bias was assessed. Results: Of the citations retrieved, eight studies including 30,970 participants met criteria for inclusion in the primary analysis, reporting 195 hip fractures and 2231 total fractures. Meta-analysis of all studies showed that calcium plus vitamin D supplementation produced a statistically significant 15 % reduced risk of total fractures (SRRE, 0.85; 95 % confidence interval [CI], 0.73–0.98) and a 30 % reduced risk of hip fractures (SRRE, 0.70; 95 % CI, 0.56–0.87). Numerous sensitivity and subgroup analyses produced similar summary associations. A limitation is that this study utilized data from subgroup analysis of the Women’s Health Initiative. Conclusions: This meta-analysis of RCTs supports the use of calcium plus vitamin D supplements as an intervention for fracture risk reduction in both community-dwelling and institutionalized middle-aged to older adults.